Expression of Ki-67 and CD34 on blood and bone marrow cells of CML patients with different response to imatinib and nilotinib therapy - Perekhrestenko, T.; Melnyk, U.; Goryainova, N.; Diagil, I. (PH Akademperiodyka, 2023)
Summary. Aim: To assess the expression of Ki-67 protein and CD34 antigen on peripheral blood (PB) and bone marrow (BM) cells in chronic myelogenous leukemia (CML) patients with different response to tyrosine kinase inhibitors (TKI) imatinib (IM) and nilotinib (NI) therapy. Patients and Methods: BM aspirate and PB samples from 41 CML patients treated with IM and NI were studied by cytogenetic, molecular genetic, and flow cytometry methods. According to the response to TKIs, the patients were distributed into the optimal response, warning, and treatment failure groups. Results: The patients with optimal response to TKI therapy showed the lowest levels of Ki-67 expression in PB and BM compared with the patients from warning and falure treatment groups, however, Ki-67 expression was close to the reference values in PB (0.7 ± 0.3)%, only in NI-treated patients, The highest expression of Ki-67 in PB was observed in patients from treatment failure groups. In PB of patients who received NI and did not achieve optimal response, CD34+ cell count increased by almost 4 times compared with that in the optimal response group. The results indicated that CD34+ cell pool expanded in patients with poor response to both IM and NI. In patients with optimal response to NI therapy, CD34+ cell counts in PB were within the reference range ​​and did not exceed 0.5%. Similar results were observed for Ki-67 and CD34+ in BM hematopoietic cells. Conclusions: Ki-67 expression and CD34+ cell count in PB and BM of CML patients increased with the acquisition of clonal resistance to IM and NI. NI provides a deeper molecular response compared with IM.